Integrating Participatory Data Acquisition and Modelling of Irrigation Strategies to Enhance Water Productivity in a Small‐Scale Irrigation Scheme in Tigray, Ethiopia. (7th March 2018) - Habtu, Solomon; Erkossa, Teklu; Froebrich, Jochen; Tquabo, Filmon; Fissehaye, Degol; Kidanemariam, Tesfay; Xueliang, Cai
Abstract: Application of participatory modelling to water‐saving strategies in smallholder farming is rare. Farmer‐preferred and efficient strategies were identified through participatory modelling. The farmers' basin irrigation and scheduling (I), farmers' scheduling with furrow strategy (II), farmers' scheduling with alternate furrow strategy (III) and scheduling at 55% maximum allowable depletion (MAD) (IV) were evaluated for maize ( Zea mais ) and barley ( Hordeum vulgare ) using the FAO AquaCrop model. The results showed that I resulted in over‐irrigation for maize and under‐irrigation for barley, while IV resulted in maximum yield (8.6 t ha ‐1 for maize and 2 t ha ‐1 for barley) with maximum (1.8 kg m ‐3 ) and minimum (0.8 kg m ‐3 ) water productivity of maize under IV and I, respectively. A shift from I to IV (most preferred strategy by farmers) can save 8440 mm of water, which can possibly bring back 18.5 ha of land into irrigation. It is essential to interact with farmers on a basis of mutual comprehension to increase their trust and to lay a base for discussion, awareness raising and decision making. The transdisciplinary approach, Community of Practice (CoP) and Learning Practice Alliance (LPA) were appropriate platforms for participation. The increased crop yield and water productivity may contribute to ecological and economical sustainability and social equity. Copyright © 2018 John Wiley & Sons, Ltd. Résumé: L'application de la modélisation participative sur les stratégies d'économie d'eau dans les petites exploitations agricoles est rare. Les stratégies privilégiées par les agriculteurs et efficaces ont été identifiées grâce à la modélisation participative. L'irrigation par bassin et sa programmation par les agriculteurs (I), la stratégie des agriculteurs pour la programmation de l'irrigation à la raie (II), la stratégie des agriculteurs pour la programmation de l'irrigation à la raie avec alternance de sillon (III) et une programmation au seuil de 55% du prélèvement maximal permis (IV) ont été évalués pour le maïs ( Zea mais ) et l'orge ( Hordeum vulgare ) en utilisant le modèle FAO AquaCrop. Les résultats ont montré que I a entraîné une surirrigation pour le maïs et une irrigation insuffisante pour l'orge, tandis que IV a donné un rendement maximal (8.6 t ha ‐1 pour le maïs et 2 t ha ‐1 pour l'orge); la productivité de l'eau pour le mais a été au maximum de1.8 kg m ‐3 et au minimum de 0.8 kg m ‐3 pour IV et I, respectivement. Un passage de I (stratégie préférée par les agriculteurs) à IV peut permettre d'économiser 8440 mm d'eau, qui peuvent éventuellement servir à irriguer un supplément de 18.5 ha de terres. Il est essentiel d'interagir avec les agriculteurs sur une base de compréhension mutuelle pour accroître leur confiance et pour établir des bases de discussion, de sensibilisation et de prise de décision. L'approche transdisciplinaire, la Communauté de pratique (CdP), et l'Alliance des pratiques d'apprentissage (APL), étaient des plateformes appropriées pour la participation. L'augmentation du rendement des cultures et de la productivité de l'eau peut également contribuer à la durabilité écologique et économique et à l'équité sociale. Copyright © 2018 John Wiley & Sons, Ltd.